The Anti-Tumor Mechanism and Target of Triptolide Based on Network Pharmacology and Molecular Docking - Zou, Tao; Huang, Yuanqiong; Hu, Yifan; Wu, Mingyu; Zhao, Yueshui; Du, Fukuan; Li, Mingxing; Wu, Xu; Ji, Huijioa; Kaboli, Parham J.; Wang, Shurong; Xiao, Zhangang; et al. (Recent Patents on Anti-Cancer Drug Discovery, 2021)
Background: According to the special physiological and pharmacological activities of natural compounds, many drugs with special therapeutic effects have been developed. The Triptolide (TP) is a natural anti-tumor drug with a world patent, but its target and mechanism are yet unknown. Objective: The study aims to explore and predict the target and mechanism of TP on Non-Small Cell Lung Cancer (NSCLC), Pancreatic Cancer (PC) and Colorectal Cancer (CC) through network pharmacology technology. Methods: We screened the core targets of TP with NSCLC, PC and CC, respectively, and carried out network analysis, enrichment analysis and ligand-receptor docking to clarify its potential pharmacological mechanism. Results: By screening the core genes between TP with NSCLC, PC and CC, respectively, it was found that PTGS2 was the common target gene in the three cancers. NSCLC, CCL2, IL6, HMOX1 and COL1A1 are the specific target genes, while MMP2, JUN, and CXCL8 are the specific target genes in PC. In CC, the specific target genes includeERBB2, VEGFA, STAT1 and MAPK8. In enrichment analysis, it was found that the NF- ΚB, toll-like receptors and IL-17 signaling pathway were mainly involved in TP for these cancers. The binding energy of TP to the core target is less than that of cyclophosphamide. Conclusion: This study preliminarily revealed that TP may prevent and treat cancers through multiple targets and pathways. The possible mechanisms of TP include regulating immune and inflammatory responses, promoting apoptosis and inhibiting tumor development. It shows that TP may have potential in treating kinds of tumors.
Keywords: Colorectal cancer